Study of Living Hadith on the Wiridan Tradition After Dawn Prayer Until Isyrâq in Banjar Society, Kalimantan Selatan - Akhmad Sagir; Riza Saputra; Hanafi; Latifah Abdul Majid (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Various religious practices flourish in Indonesia, particularly amidst the development of Islamic studies discourse. In this context, the tradition of wiridan after the Fajr prayer until isyrâq (mid-morning) serves as tangible evidence of the enduring religious traditions within the Banjar community. Initial assumptions suggest a strong connection between this tradition and prophetic hadiths, as the dzikir and other practices performed until isyrâq are mentioned in the hadiths. Based on this reality, this study specifically examines the form, motivation, and significance of the implementation of this tradition. Through the living hadith approach, the research findings reveal that the transmission of hadiths concerning dzikir and utilizing the time for worship until isyrâq is received diversely, leading to the emergence of various forms and variations of worship. From the perspective of functional reception, the Banjar community perceives the virtues of wiridan after Fajr until isyrâq, which is tied to their understanding and interpretation of the term dzikir in the hadith texts as a form of exegetical reception. Furthermore, dzikir is interpreted in four categories: dzikir through tasbih, dzikir through Quranic recitation, dzikir through religious study sessions, and dzikir through remembrance of Allah. On the aesthetic side, the unique rhythm and manner of reciting wirid among the Banjar community are evident. Another significant aspect is the prominent role of religious leaders and pesantren within the community, where the tradition has grown stronger and is consciously upheld.